Psychological and social analysis of collective trauma: the enduring lessons learned 20 years after the September 11th, terrorist attacks - Marques Barbosa Nasciutti, Fabiana; Rahbari-Jawoko, Mojgan (Reflexão, 2021)
Incidents that have a fatal impact on civilians have historically had a long-lasting impact on the psyche of those who witnessed it. The politicized September 11, 2001, terrorist attacks on the United States has been the most significant historical event of the 21st century, with major global consequences. The ongoing threats of terrorism the 9/11 incidents initiated have transformed public attitudes, socially and politically, and impacted the way people have related to one another both within the United States and globally. This paper critically examines the (i) enduring lessons learned 20 years after the tragic incidents of 9/11; (ii) global psychological response to 9/11 from a cultural-historical perspective; (iii) the broader social and socio-political impacts; interplay between identity politics, national security concerns and risks, prejudice, exclusion, and religious intolerance the events have triggered within the United States and globally; and how social media, fast information, and fake news have influenced critical thinking globally. The paper particularly explores how 9/11 could potentially impact an individual’s propensity for religious fundamentalism and prejudice and intolerance towards those who are unfamiliar.